PECULIARITIES OF ADVERTISING IN E-COMMERCE - I. Soklakova; I. Surat (Вестник университета)
The functions and methods of modern advertising, substantiates the role of advertising in the development of the brand are discussed. The possibilities of the Internet for the development of electronic commerce are described. The advantages of Internet commerce and types of e-commerce are analyzed. The volume of the online commerce market in the consumer goods sector, commerce, its positive and negative aspects are revealed in comparison with the generally accepted trade. It is concluded that the use of electronic commerce for small, medium and large businesses.